Peningkatan Kompetensi Keterampilan Peserta Didik Berbantuan LKPD Berbasis Model Discovery Learning pada Materi Fluida - Pratiwi, Nadya; Yulkifli, Yulkifli (Universitas Islam Negeri Raden Intan Lampung, 2019)
Abstract: Lack of practical activities in schools can result in a decrease in the creativity of students. worksheets based on the discovery learning model in them trigger students to think creatively and critically. The sampling technique is cluster random sampling. The purpose of this study is to look at the improvement of skills competencies which are assisted by student worksheets based on the discovery learning model. The data analysis technique is testing hypotheses where there is a difference which means the use of this student worksheet. Hypothesis testing conditions are to carry out normality tests for skill scores from both sample classes and homogeneity tests to see the distribution of values from two sample classes that have homogeneous data. after treatment is obtained, the average value of the skills of the experimental class is 78.62 and for the control class is 70.10.Abstrak: Kurangnya kegiatan praktikum di sekolah dapat mengakibatkan penurunan kreativitas siswa. lembar kerja berbasis model discovery learning di dalamnya memicu siswa untuk berpikir kreatif dan kritis. Teknik pengambilan sampel adalah cluster random sampling. Tujuan dari penelitian ini adalah untuk melihat peningkatan kompetensi keterampilan yang dibantu oleh lembar kerja siswa berdasarkan pada model pembelajaran penemuan. Teknik analisis data menguji hipotesis di mana ada perbedaan yang berarti penggunaan lembar kerja siswa ini. syarat pengujian hipotesis adalah untuk melakukan tes normalitas untuk skor keterampilan dari kedua kelas sampel dan tes homogenitas untuk melihat distribusi nilai dari dua kelas sampel yang memiliki data homogen. setelah perawatan diperoleh, nilai rata-rata keterampilan dari kelas eksperimen adalah 78,62 dan untuk kelas kontrol adalah 70,10.